Short-term caloric restriction in db/db mice improves myocardial function and increases high molecular weight (HMW) adiponectin. (December 2016) - Xu, X. Julia; Babo, Erma; Qin, Fuzhong; Croteau, Dominique; Colucci, Wilson S.
Abstract: Background: Obesity and metabolic syndrome lead to the development of metabolic heart disease (MHD) that is characterized by left ventricular hypertrophy (LVH), diastolic dysfunction, and increased mitochondrial ROS. Caloric restriction (CR) is a nutritional intervention that protects against obesity, diabetes, and cardiovascular disease. Healthy adipose tissue is cardioprotective via releasing adipokines such as adiponectin. We tested the hypothesis that CR can ameliorate MHD and it is associated with improved adipose tissue function as reflected by increased circulating levels of high molecular weight (HMW) adiponectin and AMP-activated protein kinase (AMPK) in db/db mice. Methods: Genetically obese db/db and lean db/ + male mice were fed either ad libitum or subjected to 30% CR for 5 weeks. At the end of the study period, echocardiography was carried out to assess diastolic function. Blood, heart, and epididymal fat pads were harvested for mitochondrial study, ELISA, and Western blot analyses. Results: CR reversed the development of LVH, prevented diastolic dysfunction, and decreased cardiac mitochondrial H2 O2 in db/db ( vs. ad lib ) mice. These beneficial effects on the heart were associated with increased circulating level of HMW adiponectin. Furthermore, CR increased AMPK and eNOS activation in white adipose tissue of db/db mice, but not in the heart. Conclusions: These findings indicate that even short-term CR protects the heart from MHD. Whether the beneficial effects of CR on the heart could be related to the improved adipose tissue function warrants future investigation.